Correction to: Area-Restricted Search in Magellanic Woodpeckers: Importance of Tree Senescence, Forest Composition and Open Habitats (Journal of Ornithology, 2021 10.1007/S10336-021-01878-W) - Vergara-Egert, P; Caro-Alarcon, D (Springer Science and Business Media Deutschland GmbH, 2021)
A correction to this paper has been published: https://doi.org/10.1007/s10336-021-01888-8. © 2021, Deutsche Ornithologen-Gesellschaft e.V.